Wet-chemical polyaniline nanorice mass-production for electrochemical supercapacitors - Shaikh, ShoyebMohamad F.; Lim, Ji Yeon; Mane, Rajaram S.; Han, Sung-Hwan; Ambade, Swapnil B.; Joo, Oh-Shim (ELSEVIER SCIENCE SA, 2012)
One pot run mass-production of polyaniline (PANI) nanorice is carried out using a simple room temperature ingenious low temperature wet-chemical method. Different bondings are identified using Fourier transform infrared spectroscopy analysis. Crystalline structure, due to presence of well-defined rings in selected area electron diffraction pattern, and nanorice morphology, from the scanning electorn miscropy photoimages, of as-prepared PANI are confirmed. Using high-resolution trasmission electron microscopy digital photoimage 0.46 nm and 0.37 nm fringe widths are monitored. Surface area of 41.06 m(2) g(-1) is justified from the adsorption-desorption isotherms. The PANI nanorice electrode reveals 17.33 Wh kg(-1) energy density and the 480W kg(-1) power density due to significant inner charge contribution (68.28 C g(-1)) compared to outer charge. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: NANOCOMPOSITE; PERFORMANCE; CAPACITANCE; RUO2